Identifying Factors that Influence Management of Competitiveness of Industry in Regions of Ukraine - Obolentseva Larysa V. (Problemi Ekonomiki, 2018)
In the paper, based on a variance analysis, the factors influencing management of competitiveness of industry in regions of Ukraine are identified. The cumulative values of the result indicator and gradations of an influence factor for a factorial analysis of industrial complexes are determined; the results of the single-factor variance analysis of Prydniprovskyi, Slobozhansky, and Polissia regions for 2013-2017 are presented. In the course of the numerical experiment to find the weight coefficients for the factors influencing competitiveness of industrial complexes in Prydniprovskyi, Slobozhansky, and Polissia regions, factors influencing performance efficiency of industry are identified. On the basis of the conducted factorial analysis, it is concluded that in the crisis years, the values of all indicators are unpredictable, at stabilization almost all factors show a tendency to a slow growth. It is revealed that the influence of the most important factors – level of capital investments and innovative activity of industry – is insufficient for all regions, which should be taken into account when building competitive strategies for management of regional industrial complexes.